NOT JUST METAPHOR; ENVIRONMENTAL SELF-CLEANING PROGRAM FOR LEPROSY AT BABAT JERAWAT SURABAYA - Moordiati; Ikhsan Rosyid Mujahidul Anwary; Iswahyudi (Universitas Airlangga, 2022)
This article departs from the results of community service activities in increasing knowledge about personal and environmental hygiene, especially for leprosy sufferers (people) who are in one shelter (colony), namely those in the Surabaya City area. Ideally, in many cases, their situation will be much better if they live and live in a shelter (colony), ranging from life insurance such as food and drink to health. However, in fact such things are not or have not been found in these shelters, not a few of them have actually remained unchanged. In addition to his physical condition which still often looks dirty, the environment in which he lives can also be said to be very far from comfortable as a place that allows him to live. The absence of such changes is certainly a big question mark why there are no or no changes that they should have been able to get easily while in the shelters. This is a big question that he deliberately wants to understand through knowledge-building activities, mainly on the importance of maintaining personal hygiene and environmental hygiene, considering that this issue is actually an important issue that has been ignored by most leprosy sufferers. And from the results of this activity, it seems that there is a change in behavior in leprosy people regarding maintaining personal and environmental hygiene, although they do not achieve maximum results as they are treated for people who are not affected or suffer from leprosy. Changes that can be seen after the existence of this activity program include the re-use of personal hygiene tools (soap and toothpaste) to awareness to keep their living environment clean.